(untitled) (Pedagogy of Higher and Secondary Education, 2004)
In the article the ways of the inner personality’s development in the conditions of humanizing education, the historical aspect of this problem and the modern approaches to its solving are discovered. The comparative analysis of the concepts “moral upbringing” and “inner development is realized the interrelationship of a personality’s inner and social coming-to-be is emphasized.